An Efficient Multimodal Nature‐Inspired Unmanned Aerial Vehicle Capable of Agile Maneuvers. (20th January 2023) - Sufiyan, Danial; Win, Luke Soe Thura; Win, Shane Kyi Hla; Pheh, Ying Hong; Soh, Gim Song; Foong, Shaohui
Abstract : Unmanned Aerial Vehicles In article number 2200242, Shaohui Foong present a nature‐Inspired Unmanned Aerial Vehicle (UAV). Drawing inspiration from maple seed autorotation, an efficient rotor‐wing mode is added on top of a tail‐sitter and fixed‐wing mode, forming a versatile three‐mode UAV which can seamlessly switch modes mid‐air, unlike typical hybrid UAVs that only consist of two. This platform achieves efficient hover while retaining the flexibility to enter more agile states.